Antibiotics in acute bronchitis: a meta-analysis - Bent, Stephen; Saint, Sanjay; Vittinghoff, Eric; Grady, Deborah (The American journal of medicine, 1999)
PURPOSE: Most patients with acute bronchitis who seek medical care are treated with antibiotics, although the effectiveness of this intervention is uncertain. We performed a meta-analysis of randomized, controlled trials to estimate the effectiveness of antibiotics in the treatment of acute bronchitis. SUBJECTS AND METHODS: English-language studies published January 1966 to April 1998 were retrieved using MEDLINE, bibliographies, and consultation with experts. Only randomized trials that enrolled otherwise healthy patients with a diagnosis of acute bronchitis, used an antibiotic in the treatment group and a placebo in the control group, and provided sufficient data to calculate an effect size were included. RESULTS: We identified eight randomized controlled trials that satisfied all inclusion criteria. These studies used one of three antibiotics (erythromycin, doxycycline, trimethoprim/sulfamethoxazole). The use of antibiotics decreased the duration of cough and sputum production by approximately one-half day (summary effect size 0.21; 95% CI, 0.05 to 0.36). For specific symptoms, there were nonsignificant trends favoring the use of antibiotics: a decrease of 0.4 days of purulent sputum (95% CI, −0.1 to 0.8), a decrease of 0.5 days of cough (95% CI, −0.1 to 1.1), and a decrease of 0.3 days lost from work (95% CI, −0.6 to 1.1). CONCLUSION: This meta-analysis suggests a small benefit from the use of the antibiotics erythromycin, doxycycline, or trimethoprim/sulfamethoxazole in the treatment of acute bronchitis in otherwise healthy patients. As this small benefit must be weighed against the risk of side effects and the societal cost of increasing antibiotic resistance, we believe that the use of antibiotics is not justified in these patients.